Learning at the museum frontiers [ identity, race, and power - Golding, Vivien (Ashgate Publication, 2009)
In 'Learning at the Museum Frontiers', Viv Golding argues that the museum has the potential to function as a frontier: a zone where learning is created, new identities are forged and new connections made between disparate groups and their own histories. Drawing on a range of theoretical perspectives from Foucault to Morrison, as well as her own professional experience in museum education over a ten-year period, Golding offers an important theoretical and empirical contribution to the debate on the value of museums and what they can contribute to society.